Managing the politics of value propositions. (December 2014) - Corvellec, Hervé; Hultman, Johan
This article contributes to the ongoing discussion, revived by the service-dominant logic thesis, on value propositions in service organizations. Against a backdrop of understanding value as a pluralistic social construct that takes place across different institutionalized practices of valuation or regimes of value, we argue that value propositions transcend the immediate localness of both value in exchange and value in use. Correspondingly, we claim that service practitioners may draw advantages from engaging with a politics of value that addresses multiple regimes of value, whether commensurable or not. A case study of waste management services in Sweden serves as an illustration of such a politics that combines practical, economic, political, and environmental aspects of value propositions.